2013
DOI: 10.1186/1475-2840-12-50
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of triptolide improve left ventricular function in a rat model of diabetic cardiomyopathy

Abstract: AimsGiven the importance of inflammation in the onset and progression of diabetic cardiomyopathy, we investigated the potential protective effects of triptolide, an anti-inflammatory agent, in streptozotocin-induced diabetic rat model and in H9c2 rat cardiac cells exposed to high glucose.Methods and resultsDiabetic rats were treated with triptolide (100, 200, or 400 μg/kg/day respectively) for 6 weeks. At the end of this study, after cardiac function measurements were performed, rats were sacrificed and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 39 publications
2
64
0
Order By: Relevance
“…T. wilfordii contains >100 bioactive compounds and triptolide is one of the major biologically active components. In vivo and in vitro experiments have demonstrated that triptolide has a role in numerous immune disorders, including multiple sclerosis, colitis, lupus nephritis and transplant rejection (6,15,16). The anti-inflammatory activity of triptolide not only activates immune cells, such as T cells and monocytes, Anti-inflammatory effects of triptolide by inhibiting the NF-κB signalling pathway in LPS-induced acute lung injury in a murine model but also resident tissue cells (17,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T. wilfordii contains >100 bioactive compounds and triptolide is one of the major biologically active components. In vivo and in vitro experiments have demonstrated that triptolide has a role in numerous immune disorders, including multiple sclerosis, colitis, lupus nephritis and transplant rejection (6,15,16). The anti-inflammatory activity of triptolide not only activates immune cells, such as T cells and monocytes, Anti-inflammatory effects of triptolide by inhibiting the NF-κB signalling pathway in LPS-induced acute lung injury in a murine model but also resident tissue cells (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…This is caused by inflammation-related stimuli, primarily sepsis and pneumonia, which lead to leukocyte migration and overproduction of pro-inflammatory mediators, including interleukin (IL)-6, IL-8 and tumour necrosis factor-α (TNF-α) (3). ALI is a fatal disease that can cause persistent respiratory failure and multiorgan dysfunction, and patients with ALI may be dependent on mechanical ventilation (4)(5)(6). Although intensive care has been greatly improved, the mortality rate caused by ALI is between 40 and 70%, and ~200,000 individuals are affected by the condition in America every year.…”
Section: Introductionmentioning
confidence: 99%
“…It was first isolated from the root extract and characterized in 1972 as a diterpenoid triepoxide lactone containing 18 (4→3) abeo-abietane backbones Figure 1. Just after its isolation, it was established as an anti-tumor, 11 anti-inflammatory, 12 immunosuppressive, 13,14 and anti-fertility drug. 15,16,17,18 As compared to other anti-tumor drug, triptolide has comparable or superior effects, especially against p53 mutated or multi-drug resistant cell lines.…”
Section: Triptolide Chemistrymentioning
confidence: 99%
“…On the day one before streptozotocin injection, 5 and 11 weeks after streptozotocin induction cardiac function was assessed by echocardiography using GE Vivid 7 ultrasound with 10-MHz transducer (General Electric, USA) as described by Wen et al (2013) with slight modifications. The rats were exposed to isoflurane anesthesia (3%) and were placed in the supine position and the left ventricular end-diastolic diameter (LVEDD) and left ventricular end-systolic diameter (LVESD) were measured on the parasternal left ventricular long axis view.…”
Section: Assessment Of Cardiac Functionmentioning
confidence: 99%
“…Accumulating evidences suggest varied mechanisms to be associated with diabetic cardiomyopathy (Wen et al, 2013), including excessive generation of reactive oxygen species (ROS) (Kajstura et al, 2001;Pacher et al, 2007;Wang et al, 2009), activation of inflammatory signals, transcription factors as NF-κB (Aragno et al, 2006;Wang et al, 2009), poly (ADP-ribose) polymerase (Pacher et al, 2002), MAPK cascades (Westermann et al, 2006;Thandavarayan et al, 2009), down-regulation of survival pathways as Akt (Van Linthout et al, 2008), alterations in the extracellular matrix composition (Westermann et al, 2007) and activation of cell death pathways (Frustaci et al, 2000).…”
Section: Introductionmentioning
confidence: 99%